Sistema web de simulação de investimento financeiro - Ferreira, Philipe Matheos Gama (Brasil, 2024)
The purpose of this work is the development of a financial investment simulation system with the purpose of helping investors in the investment process and to recognize which are the best returns within the capital market. The system will work in the web environment and will have a friendly, clean and responsive interface. The following resources will be available in the application: user registration, login system, financial investment simulation, investment report, investor profile and financial market information area. The system aims to serve users interested in investments.